Aspek Komunikasi dalam Pengajaran Bahasa - S., Setyadi, Drs. (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 1981)
This article discusses the communicative aspects of foreign language teaching, particularly English, by tracing the development of teaching methods and theories alongside advances in linguistics. The early stage was characterized by the traditional grammar-translation approach, later shifting to structural methods such as the audio-lingual approach, and eventually transforming into generative and cognitive perspectives. The article also highlights teaching practices around the 1960s, which emphasized pattern practice to master grammatical structures through repetition and error correction. These paradigm shifts illustrate the transition from passive learning to viewing language as a tool for active communication. Thus, the article underscores that language teaching should not be confined to grammar instruction but should also focus on developing broader communicative competence.